Program Shalat Berjamaah dalam Pembentukan Karakter Islami Siswa Sekolah Menengah Atas - Joko Utomo; Mindani Mindani (Academia Edu Cendekia Indonesia (AEDUCIA), 2025)
Background; Character education supports Islamic values in schools, with congregational prayer viewed as a means to instill moral and spiritual principles. However, the implementation and impact of such programs on students’ character development remain underexplored. Objective: This study aims to examine the implementation of the congregational prayer program in strengthening the Islamic character of high school students, particularly focusing on the development of gratitude. Method: The research employed a qualitative approach with a phenomenological paradigm. It was conducted at SMA Muhammadiyah 4 Bengkulu in 2022. Data were collected through three primary techniques: (1) participant observation, (2) in-depth interviews, and (3) documentation. The analysis was carried out using the deduction, induction, and comparison methods. Result: The findings reveal that the implementation of Dhuha and Zuhur congregational prayers contributes significantly to shaping students' gratitude character. This development is evident in three dimensions: physical (behavioral discipline), psychological (emotional awareness and sincerity), and social (togetherness and mutual respect). Conclusion: The congregational prayer program effectively fosters Islamic character in students, particularly the value of gratitude. Routine practice and a supportive school environment play a critical role in reinforcing this character. Contribution: This research provides valuable insights into how religious practices, such as congregational prayer, can be integrated into school programs to support character education. It serves as a scientific reference for educators and policymakers aiming to strengthen Islamic values in educational institutions.